Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Given the functions [tex]\( g(x) = x^2 \)[/tex] and [tex]\( h(x) = -x^2 \)[/tex], let's analyze the truthfulness of each statement step by step:
1. For any value of [tex]\( x \)[/tex], [tex]\( g(x) \)[/tex] will always be greater than [tex]\( h(x) \)[/tex]:
- [tex]\( g(x) = x^2 \)[/tex]
- [tex]\( h(x) = -x^2 \)[/tex]
If we compare [tex]\( g(x) \)[/tex] and [tex]\( h(x) \)[/tex], we get:
[tex]\[ x^2 > -x^2 \][/tex]
This translates to:
[tex]\[ 2x^2 > 0 \quad \text{which is always true for all \( x \)}. \][/tex]
Therefore, this statement is true.
2. For any value of [tex]\( x \)[/tex], [tex]\( h(x) \)[/tex] will always be greater than [tex]\( g(x) \)[/tex]:
Using the same functions:
[tex]\[ -x^2 > x^2 \quad \text{which is never true for any real \( x \)} \][/tex]
This statement is false.
3. [tex]\( g(x) > h(x) \)[/tex] for [tex]\( x = -1 \)[/tex]:
Evaluating the functions at [tex]\( x = -1 \)[/tex]:
[tex]\[ g(-1) = (-1)^2 = 1 \][/tex]
[tex]\[ h(-1) = -(-1)^2 = -1 \][/tex]
Clearly,
[tex]\[ 1 > -1 \][/tex]
Thus, this statement is true.
4. [tex]\( g(x) < h(x) \)[/tex] for [tex]\( x = 3 \)[/tex]:
Evaluating the functions at [tex]\( x = 3 \)[/tex]:
[tex]\[ g(3) = 3^2 = 9 \][/tex]
[tex]\[ h(3) = -(3)^2 = -9 \][/tex]
Clearly,
[tex]\[ 9 > -9 \][/tex]
This statement is false because [tex]\( g(x) \)[/tex] is not less than [tex]\( h(x) \)[/tex]; it is greater.
5. For positive values of [tex]\( x \)[/tex], [tex]\( g(x) > h(x) \)[/tex]:
For [tex]\( x > 0 \)[/tex]:
[tex]\[ g(x) = x^2 \quad \text{and} \quad h(x) = -x^2 \][/tex]
It is clear that:
[tex]\[ x^2 > -x^2 \][/tex]
Hence for all positive [tex]\( x \)[/tex]:
[tex]\[ g(x) > h(x) \][/tex]
Therefore, this statement is true.
6. For negative values of [tex]\( x \)[/tex], [tex]\( g(x) > h(x) \)[/tex]:
For [tex]\( x < 0 \)[/tex]:
[tex]\[ g(x) = x^2 \quad \text{and} \quad h(x) = -x^2 \][/tex]
Even for negative [tex]\( x \)[/tex]:
[tex]\[ x^2 > -x^2 \][/tex]
Hence for all negative [tex]\( x \)[/tex]:
[tex]\[ g(x) > h(x) \][/tex]
Therefore, this statement is true.
Summarizing the true statements:
- [tex]\( g(x) > h(x) \)[/tex] for [tex]\( x = -1 \)[/tex] (Statement 3)
- For positive values of [tex]\( x \)[/tex], [tex]\( g(x) > h(x) \)[/tex] (Statement 5)
- For negative values of [tex]\( x \)[/tex], [tex]\( g(x) > h(x) \)[/tex] (Statement 6)
Thus, the true statements are:
[tex]\( \boxed{3, 5, 6} \)[/tex]
1. For any value of [tex]\( x \)[/tex], [tex]\( g(x) \)[/tex] will always be greater than [tex]\( h(x) \)[/tex]:
- [tex]\( g(x) = x^2 \)[/tex]
- [tex]\( h(x) = -x^2 \)[/tex]
If we compare [tex]\( g(x) \)[/tex] and [tex]\( h(x) \)[/tex], we get:
[tex]\[ x^2 > -x^2 \][/tex]
This translates to:
[tex]\[ 2x^2 > 0 \quad \text{which is always true for all \( x \)}. \][/tex]
Therefore, this statement is true.
2. For any value of [tex]\( x \)[/tex], [tex]\( h(x) \)[/tex] will always be greater than [tex]\( g(x) \)[/tex]:
Using the same functions:
[tex]\[ -x^2 > x^2 \quad \text{which is never true for any real \( x \)} \][/tex]
This statement is false.
3. [tex]\( g(x) > h(x) \)[/tex] for [tex]\( x = -1 \)[/tex]:
Evaluating the functions at [tex]\( x = -1 \)[/tex]:
[tex]\[ g(-1) = (-1)^2 = 1 \][/tex]
[tex]\[ h(-1) = -(-1)^2 = -1 \][/tex]
Clearly,
[tex]\[ 1 > -1 \][/tex]
Thus, this statement is true.
4. [tex]\( g(x) < h(x) \)[/tex] for [tex]\( x = 3 \)[/tex]:
Evaluating the functions at [tex]\( x = 3 \)[/tex]:
[tex]\[ g(3) = 3^2 = 9 \][/tex]
[tex]\[ h(3) = -(3)^2 = -9 \][/tex]
Clearly,
[tex]\[ 9 > -9 \][/tex]
This statement is false because [tex]\( g(x) \)[/tex] is not less than [tex]\( h(x) \)[/tex]; it is greater.
5. For positive values of [tex]\( x \)[/tex], [tex]\( g(x) > h(x) \)[/tex]:
For [tex]\( x > 0 \)[/tex]:
[tex]\[ g(x) = x^2 \quad \text{and} \quad h(x) = -x^2 \][/tex]
It is clear that:
[tex]\[ x^2 > -x^2 \][/tex]
Hence for all positive [tex]\( x \)[/tex]:
[tex]\[ g(x) > h(x) \][/tex]
Therefore, this statement is true.
6. For negative values of [tex]\( x \)[/tex], [tex]\( g(x) > h(x) \)[/tex]:
For [tex]\( x < 0 \)[/tex]:
[tex]\[ g(x) = x^2 \quad \text{and} \quad h(x) = -x^2 \][/tex]
Even for negative [tex]\( x \)[/tex]:
[tex]\[ x^2 > -x^2 \][/tex]
Hence for all negative [tex]\( x \)[/tex]:
[tex]\[ g(x) > h(x) \][/tex]
Therefore, this statement is true.
Summarizing the true statements:
- [tex]\( g(x) > h(x) \)[/tex] for [tex]\( x = -1 \)[/tex] (Statement 3)
- For positive values of [tex]\( x \)[/tex], [tex]\( g(x) > h(x) \)[/tex] (Statement 5)
- For negative values of [tex]\( x \)[/tex], [tex]\( g(x) > h(x) \)[/tex] (Statement 6)
Thus, the true statements are:
[tex]\( \boxed{3, 5, 6} \)[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.